Characterization of the insulator barrier and the superconducting transition temperature in GdBa2Cu3O7−δ/BaTiO3 bilayers for application in tunnel junctions - Navarro, H.; Yang, I.; Sirena, M.; Kim, J.; Haberkorn, N.; Haberkorn, Néstor (AIP Publishing, 2015)
Fil: Navarro, H. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina